Interference in Coagulation Testing: Focus on Spurious Hemolysis, Icterus, and Lipemia - Lippi, Giuseppe; Plebani, Mario; Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2013)
The chance that errors might jeopardize the quality of testing is inherently present throughout the total testing process, especially in the preanalytical phase. In the coagulation laboratory, as well as in other areas of diagnostic testing, spurious hemolysis, icteria, and lipemia in test samples represent by far the leading diagnostic challenges. Interference in hemostasis testing due to spurious hemolysis is attributed to both analytical and biologic elements, namely high absorbance of cell-free hemoglobin at wavelengths used by optical instrumentation and release of both cytoplasmatic and plasma membrane molecules (e.g., tissue factor, proteases, phospholipids, and ADP) that can spuriously activate blood coagulation and platelets. The interference attributable to hyperbilirubinemia is mostly due to spectral overlap, whereas that of hypertriglyceridemia mainly reflects elements of light scatter and volume displacement as well as direct interference of lipid particles with hemostasis. In practical terms, spurious hemolysis reflects a more generalized process of endothelial and blood cell damage, so that test results on spuriously hemolyzed specimens should be systematically suppressed. The bias attributable to hyperbilirubinemia is less significant using modern coagulometers equipped with dedicated wavelengths (i.e., with readings at 650 nm or above), so that test results in samples with a bilirubin concentration up to 20 mg/dL can still be analytically reliable. The interference observed in lipemic samples is most evident with readings using wavelengths lower than 500 nm and can hence be prevented with readings at 650 nm or above, and/or using higher dilutions of the test sample, or can be abated in high hypertriglyceridemic specimens (i.e., > 1,000 mg/dL) using high speed microcentrifugation or lipid extraction with organic solvents such as fluorine-chlorinated hydrocarbon, or lipid-clearing agents such as LipoClear (StatSpin Inc., Norwood, MA) and n-hexane.
Keywords: interference; coagulation testing; hemolysis; lipemia; errors